Long-term treatment with growth hormone in short children with nephropathic cystinosis - Wühl, Elke; Haffner, Dieter; Offner, G.; Broyer, Michel; Hoff, William van’t; Mehls, Otto (The journal of pediatrics, 2002)
Objective: The objective was to assess the efficacy and safety of growth hormone (GH) treatment in severely growth retarded children with nephropathic cystinosis during conservative treatment and during renal replacement therapy. Study design: The design was an open-labeled prospective trial with a run-in period of 1 year. Results: A total of 74 children with cystinosis (age 3.0 to 18 years) were treated with GH over a mean period of 3.1 years (range 1 to 10 years); 52 patients were receiving conservative treatment (mean age 7.1 years), 7 were receiving dialysis (12.5 years), and 15 had received a renal transplant (14.8 years). The mean standardized height (SD score) was -4.0 in the conservative treatment group, -4.4 in the dialysis group, and -4.9 in the renal transplant group. During the first treatment year, height velocity doubled in the conservative treatment group, increased by 80% in the dialysis group, and increased by 45% in renal transplant group. Within 3 years the height SD score increased by +1.6 (P <.001) in prepubertal patients receiving conservative treatment, and percentile parallel growth was maintained thereafter. These effects of GH were less expressed in peripubertal patients receiving renal replacement therapy. No major side effects were observed. Conclusion: Long-term GH treatment is safe and effective in young children with nephropathic cystinosis. GH treatment should be started early in the course of the disease if adequate nutrition and cysteamine treatment do not prevent growth retardation. (J Pediatr 2001;138:880-7)
Available online 25 May 2002
Gesehen am 11.01.2021